Cohort profile: the Biology, Affect, Stress, Imaging and Cognition (BASIC) study on perinatal depression in a population-based Swedish cohort. Issue 10 (22nd October 2019) - Axfors, Cathrine; Bränn, Emma; Henriksson, Hanna E; Hellgren, Charlotte; Kunovac Kallak, Theodora; Fransson, Emma; Lager, Susanne; Iliadis, Stavros I; Sylvén, Sara; Papadopoulos, Fotios C; Ekselius, Lisa; Sundström-Poromaa, Inger; et al.
Abstract : Purpose: With the population-based, prospective Biology, Affect, Stress, Imaging and Cognition (BASIC) cohort, we aim to investigate the biopsychosocial aetiological processes involved in perinatal depression (PND) and to pinpoint its predictors in order to improve early detection. Participants: From September 2009 to November 2018, the BASIC study at Uppsala University Hospital, Sweden, has enrolled 5492 women, in 6478 pregnancies, of which 46.3% first-time pregnancies and with an average age of 31.5 years. After inclusion around gestational week 16–18, participants are followed-up with data collection points around gestational week 32, at childbirth, as well as three times postpartum: after 6 weeks, 6 months and 1 year. At the last follow-up, 70.8% still remain in the cohort. Findings to date: In addition to internet-based surveys with self-report instruments, participants contribute with biological samples, for example, blood samples (maternal and from umbilical cord), biopsies (umbilical cord and placenta) and microbiota samples. A nested case–control subsample also takes part in cognitive and emotional tests, heart rate variability tests and bioimpedance tests. Subprojects have identified various correlates of PND of psychological and obstetric origin in addition to factors of the hypothalamic–pituitary–adrenal axis and immune system. Future plans: In parallel with the completion of data collection (final follow-up November 2019), BASIC study data are currently analysed in multiple subprojects. Since 2012, we are conducting an ongoing follow-up study on the participants and their children up to 6 years of age (U-BIRTH). Researchers interested in collaboration may contact Professor Alkistis Skalkidou (corresponding author) with their request to be considered by the BASIC study steering committee.